The Translation of Cultural Referents: From Reference to Mental Representation - Santamaria, Laura (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2010)
This article explores the cognitive information carried by cultural referents and presents a multidisciplinary approach to understanding how target audiences grasp them. I depart from the assumption that cultural referents are used in works of fiction – the examples presented here are taken from a TV sitcom – to allow the target audience to associate characters with a given sociocultural environment. Depending on the techniques used in the translation the individuals will need to make a greater effort than the target audience of the original text and some information will not be appropriately retrieved. It can help the translator to identify the critical phases in this cognitive process.